Manajemen Kesan Customer Relation pada Brand DNVB di Instagram melalui Perspektif Dramaturgi - Nailir Rochmah, Putri Erma; Suminar, Jenny Ratna; Aristi, Nindi (JURNAL LENSA MUTIARA KOMUNIKASI, 2024)
The development of the times and technology has changed the consumer communication landscape, involving social media such as Instagram as the primary medium of interaction between consumers and brands. DNVB Indonesia uses Instagram as a medium of interaction because it can reach consumers more widely. This research explores how DNVB Indonesia utilizes Customer Relationship Management (CRM) and Customer Relationship Officer (CRO) to build consumer interactions and impressions through a dramaturgical theory approach. This study uses a qualitative methodology with an intrinsic case study approach. Data was collected through interviews, observation, and documentation. The research results show that the effectiveness of Instagram use by DNVB Indonesia is supported by a communication strategy that involves the 'mini' character and the active role of CRO in building personal and relevant relationships with consumers. CROs are essential in ensuring satisfying interactions by applying dramaturgical theory to create a positive impression. This theory divides social interactions into front and back stages, with the CRO acting as an actor who must maintain the company's image in front of consumers. These findings provide strategic insights for DNVBs in managing customer expectations and creating more robust and meaningful relationships through digital interactions.